β-adrenergic signaling in mice housed at standard temperatures suppresses an effector phenotype in CD8(+) T cells and undermines checkpoint inhibitor therapy - Bucsek, Mark J. (Cancer Res, 2017)
The immune context of tumors has significant prognostic value and is predictive of responsiveness to several forms of therapy, including immunotherapy. We report here that CD8(+) T cell frequency and functional orientation within the tumor microenvironment is regulated by β(2)-adrenergic receptor (β-AR) signaling in host immune cells. We used three strategies - physiologic (manipulation of ambient thermal environment), pharmacologic (β-blockers), and genetic (β(2)-adrenergic receptor knockout mice) to reduce adrenergic stress signaling in two widely studied preclinical mouse tumor models. Reducing β-AR signaling facilitated conversion of tumors to an immunologically active tumor microenvironment with increased intra-tumoral frequency of CD8+ T cells with an effector phenotype and decreased expression of PD-1, in addition to an elevated effector CD8(+) T cell to CD4(+) regulatory T cell ratio (IFN-γ(+)CD8(+):Treg). Moreover, this conversion significantly increased the efficacy of anti-PD-1 checkpoint blockade. These data highlight the potential of adrenergic stress and norepinephrine-driven β-adrenergic receptor signaling to regulate the immune status of the tumor microenvironment and supports the strategic use of clinically available β-blockers in patients to improve responses to immunotherapy.